2011
DOI: 10.1371/journal.pone.0017199
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Telomere Length in a Bird

Abstract: Telomere dynamics are intensively studied in human ageing research and epidemiology, with many correlations reported between telomere length and age-related diseases, cancer and death. While telomere length is influenced by environmental factors there is also good evidence for a strong heritable component. In human, the mode of telomere length inheritance appears to be paternal and telomere length differs between sexes, with females having longer telomeres than males. Genetic factors, e.g. sex chromosomal inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 26 publications
7
70
1
1
Order By: Relevance
“…Indeed, results might have been different had we sampled the parents when they were chicks. Nonetheless, our findings are in accordance with previous data collected on the kakapo (Horn et al, 2011), showing maternal inheritance of telomere length in birds. The pattern of telomere length inheritance displayed in birds seems to mirror the one found in several human studies (Nordfjäll et al, 2005(Nordfjäll et al, , 2009Njajou et al, 2007) and suggests that the heterogametic sex might have a key role in offspring telomere length determination.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, results might have been different had we sampled the parents when they were chicks. Nonetheless, our findings are in accordance with previous data collected on the kakapo (Horn et al, 2011), showing maternal inheritance of telomere length in birds. The pattern of telomere length inheritance displayed in birds seems to mirror the one found in several human studies (Nordfjäll et al, 2005(Nordfjäll et al, , 2009Njajou et al, 2007) and suggests that the heterogametic sex might have a key role in offspring telomere length determination.…”
Section: Discussionsupporting
confidence: 93%
“…Most of these studies support paternal inheritance of telomere length (Nordfjäll et al, 2005(Nordfjäll et al, , 2009Njajou et al, 2007), further revealing that paternal age is a strong determinant of offspring telomere length (Unryn et al, 2005;De Meyer et al, 2007;Kimura et al, 2008;Eisenberg, 2011). Interestingly, in non-human species contrasting results reveal either bi-parental inheritance patterns, for example, male inheritance in lizards (Olsson et al, 2011) or maternal inheritance in birds (females being ZW; Horn et al, 2011). These studies report highly variable heritability estimates ranging from 0.18 to 41.…”
Section: Introductionmentioning
confidence: 92%
“…For example, a recent study on great reed warblers found significant heritability of RTL of 35-48%, as well as strong brood and maternal effects [15]. Similarly, in kakapos (Strigops habroptilus) and king penguins (Aptenodytes patagonicus), mothers and their offspring resembled each other in telomere length, but fathers and their offspring did not [16,18]. In line with these bird studies, we found a link between maternal and offspring RTL.…”
Section: Discussionsupporting
confidence: 88%
“…We also included sex in our analyses as it is a common driver of foraging behaviors in many taxa (Aho et al 1997, Codding et al 2011) including seabirds (e.g., Weimerskirch et al 1997, Welcker et al 2009). Adult male murres have longer telomeres than females (Young et al 2013), which follows the pattern seen in other bird species (Horn et al 2011). In murres, diving patterns differ by sex (Jones et al 2002), and in the Common Murre (Uria aalge), females provide more food to the chick, perhaps because males invest in themselves during the nestling phase, saving chick investment for the extended weeks of post-fledging care provided only by the male (Thaxter et al 2009).…”
Section: Introductionmentioning
confidence: 64%